Successful treatment of synchronous hairy cell leukaemia and diffuse large B cell lymphoma in a patient with severe hypercalcemia and extensive osteolytic lesions - Marković Olivera; Gotić Mirjana; Čemerikić Vesna; Divac Anica; Marisavljević Dragomir (Vojnosanitetski Pregled)
Introduction. Although secondary malignancies usually occur at different times after hairy cell leukemia (HCL) treatment, the occurrence of HCL and other malignancies at the same time is very rare. Synchronous HCL and diffuse large B-cell lymphoma (DLBCL) have not been described so far. Case report. The report presents a 62-year-old female patient with intense constitutional symptoms, hypercalcemia, pancytopenia, and osteolytic destruction of the left shoulder joint. Immunohistochemical analysis of the bone marrow revealed the presence of two cell populations: a population of HCL cells and a population of DLBCL cells with the expression of CMYC and BCL-2 proteins ("double expressor" DLBCL) and high proliferative activity (Ki-67+cells > 90%). Fluorescence in situ hybridization (FISH) analysis showed amplification of the BCL-2 gene. In addition, BRAF gene V600E mutation was detected. After intensive treatment with immunochemotherapy, radiotherapy, and bisphosphonates, the patient achieved complete remission, lasting for more than two years. Conclusion. As the association of HCL and lymphoma is very rare, diagnosis of synchronous occurrence of two lymphoproliferative diseases is a diagnostic and therapeutic challenge. It remains unclear whether DLBC and HCL originated from two different malignant clones or DLBCL developed by the transformation of HCL as the result of clonal evolution of the B-cell clone.